Is the rational thought of humanity an entelechy? Emotions and learning - Gonzalez Sarmiento, Olga (2017)
This paper studied in depth the relationship that had been explored by the Neuroscience between the emotions and human learning. It was an attempt to explain such processes originated specially on the limbic system, where all kind of positive and negative emotions are generated, without being sometimes taken into account in the educational process in a significant way. Moreover, some small but important, changes and strategies are proposed to contribute to the achievement of better learning in our students.